Management of dermatofibrosarcoma protuberans. Issue 4 (August 2021) - Badhey, Arvind K.; Tikhtman, Raisa; Tang, Alice L.
Abstract : Purpose of review: Provide an up to date review of the diagnosis, workup and treatment of dermatofibrosarcoma protuberans (DFSP). DFSP can be a challenging disease to manage and adequate understanding of the most up to date literature can help provide comprehensive treatment strategies. Recent findings: DFSP is an infiltrative cutaneous sarcoma. It tends to have deep local invasion with a high risk of local recurrence, but a low risk of distant metastasis. It presents typically as a slow growing, asymptomatic skin lesion. It presents rarely in the head and neck, only 15% of the time. Recent data has discussed the role of wide local excision (WLE) vs. Mohs surgery. In addition, for unresectable disease the role of systemic therapy and immunomodulatory agents such as Imatinib has shown success. Summary: Typically, surgical management is the first line for DFSP, however the risk for local recurrence still remains high with negative margins. Due to this risk, lifelong surveillance is required after initial diagnosis and management. Similar to other head and neck tumors, most recurrences happen within the first 3 years after treatment. DFSP can be treated with WLE or Mohs. For aggressive disease that is considered unresectable systemic therapy does exist, including molecular targeted therapies.